Strategi Ombudsman RI dalam Pencegahan Maladministrasi Penyelenggaraan Pelayanan Publik: Studi Pada Kantor Ombudsman Perwakilan Sulawesi Tenggara - Ariyanti, Milda; Amir, Muh.; Ramayana, Wa Ode Srijuna (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to determine how the ombudsman RI strategy in preventing maladministration of public service delivery and how to prevent maladministration of public service delivery. The method used in this research is descriptive qualitative research with data collection through observation, interviews, and documentation. The strategy of the ombudsman of Southeast Sulawesi representatives in preventing maladministration of public service delivery in general is still not good so that it has not been successful, especially in the goal indicator due to the lack of socialisation to the public about the ombudsman and the coverage of the ombudsman's working area which is far from the community environment in Southeast Sulawesi, then the environment because in environmental indicators both internal and external factors have not succeeded in carrying out the strategy of preventing maladministration in public service delivery in Southeast Sulawesi and in the learning indicator, the ombudsman of Southeast Sulawesi stopped cooperation between ombudsman friends so that this became inefficient due to the lack of quantity of human resources in the Southeast Sulawesi ombudsman office. The Ombudsman of Southeast Sulawesi representatives in preventing maladministration in accordance with the ombudsman regulation of the Republic of Indonesia number 41 of 2019 is still not good and not optimal, especially at the detection stage because it indirectly explains that the initiative to detect and track potential maladministration has not been carried out by the ombudsman of Southeast Sulawesi. Ombudsman sultra has carried out the entire series of prevention stages properly in accordance with applicable ombudsman regulations on procedures for preventing maladministration.